THE PORTRAYAL OF HEGEMONY AS SEEN IN SNOWPIERCER - Lasiana, Dewi Saklina; Wedawati, Mamik Tri (Journal of Language and Literature, 2021)
Snowpiercer is a sci-fi thriller movie directed by Bong Joon-ho. This movie presents the world’s survivors that live in a train creating their own economy and class system. The depiction of the movie is how power and ruling position could be achieved by conducting a process of moral and intellectual leadership rather than exercising full coercion. In Snowpiercer, Wilford as the dominant class attempts to gain power and authority to control the society through ideological indoctrination by the apparatuses. The study employs a sociological approach to literature to reveal the operation of hegemony in Snowpiercer. This study uses Antonio Gramsci’s concept of Hegemony as the main theory and Max Weber’s theory about power as supporting theory. In analyzing the data, this study uses a narrative and non-narrative approach. This study aims to describe hegemony through five stages of hegemony operation in Snowpiercer. Secondly, revealing the impact of hegemony on the subaltern class in Snowpiercer. Moreover, as the result shows that In Snowpiercer, hegemony is a process of gaining power through Indoctrinating ideology in which the role of coercive elements is necessary to maintain the power and authority obtained by the dominant class when the hegemony has weakened. This explains how hegemony conducted by Wilford lasts long and strong as it affects particular main aspects such as economic, military, education, culture, etc. Moreover, The dominant class's hegemony arises an impact on the subaltern class in the tail section, many people in the tail section get isolated, oppressed, and exploited.